Caçadores de onça: Sobre a relação homem e natureza entre os gateiros do Paru, Almeirim-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The Amazon land, since colonial times has been a space for exploring its natural resources to attend diverse cycles and international demands, these processes marked the region deeply, modifying its way of seeing, being and perceiving the world. One of these economic cycles was the hunting of mostly felines and cat-maracajá felines and using the narrative of the hunter(gateiros) of the region of Paru (Almeirim-Pa) that made this way and maintaining life, to perceive the dynamics in their territory And sociabilities.
Keywords: Homem-natureza; Território; Caça; CNPQ:: CIÊNCIAS HUMANAS